Pengembangan Bahan Ajar Berbasis Pendekatan Open Ended Untuk Meningkatkan Keterampilan Penalaran Siswa Pada Materi Faktor Kelipatan Bilangan Di SD Negeri Pangggungroyom 01 - Ikha Valenta Nosawati; Joko Sulianto; Mira Azizah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this research is to develop teaching materials on multiple factor material based on an open ended approach to improve students' reasoning abilities. This research method is RnD (Research and Development) research. The results obtained from the validation of materials and media. The results of the three material experts showed an average percentage of 86.66% and the results of the three media experts showed an average percentage of 87.57%. The results of the analysis of the fourth grade teacher response assessment obtained the results from the material assessment aspect an average percentage of 96.88% and from the media assessment aspect the average percentage got 94.45%. It can be concluded that the teaching materials developed are included in the "very good" and "very feasible" categories to be used in learning Mathematics for grade IV material for factor multiples of numbers. The conclusion that the researcher conveys is that teaching materials based on an open ended approach can be used as an alternative teaching material that can be used in learning.